Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga pada Kepuasan Konsumen (Studi Empiris pada Masyarakat Middle Income Pelanggan Gerai Ritel Jejaring Modern di Yogyakarta) - Lukas Agung Heriputranto (JEMAP, 2018)
The purpose of the study is to know the influence of product quality,  service quality, and price  on customer satisfaction on the  middle income society the customers of  modern networking outlets retail in Yogyakarta. The population  of this  research are middle income society ascustomer of modern networking outlets retail in Yogyakarta. The sample of this research as much as 100 respondents. The sampling technique is purposive sampling. Data collection is done by  questionnaire.  Data analysis techniques using multiple linear regression analysis. The results showed that: (1) the product quality, service quality, and prices simultaneouslyinfluence  on customer satisfaction. (2) the product quality, service quality, and price  partially positive influenc  on customer satisfaction.